2020
DOI: 10.32607/actanaturae.10967
|View full text |Cite
|
Sign up to set email alerts
|

Palette of Luciferases: Natural Biotools for New Applications in Biomedicine

Abstract: Optoanalytical methods based on using genetically encoded bioluminescent enzymes,luciferases, allow one to obtain highly sensitive signals, are non-invasive, and require no external irradiation. Bioluminescence is based on the chemical reaction of oxidation of a low-molecular-weight substrate (luciferin) by atmospheric oxygen, which is catalyzed by an enzyme (luciferase). Relaxation of the luciferin oxidation product from its excited state is accompanied by a release of a quantum of light, which can be detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 117 publications
(127 reference statements)
0
14
0
Order By: Relevance
“…Beetle bioluminescence systems belong to one of the most practically important and well-understood groups of bioluminescence reactions. The ability to emit light has evolved in several Coleoptera families including fireflies (Lampyridae), click beetles (Elateridae) and railroad worms (Phengodidae), with the light emission wavelength ranging from green to red (540-640 nm) depending on the beetle species (Viviani et al, 2011;Kotlobay et al, 2020). All known beetle bioluminescence system depend on a common substrate (S)-2-(6-hydroxy-2-benzothiazolyl)-2-thiazoline-4carboxylic acid, commonly known as D-luciferin (Figure 1), which consists of two structural units, benzothiazole and thiazoline rings (Shimomura and Yampolsky, 2019).…”
Section: D-luciferin-dependent Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Beetle bioluminescence systems belong to one of the most practically important and well-understood groups of bioluminescence reactions. The ability to emit light has evolved in several Coleoptera families including fireflies (Lampyridae), click beetles (Elateridae) and railroad worms (Phengodidae), with the light emission wavelength ranging from green to red (540-640 nm) depending on the beetle species (Viviani et al, 2011;Kotlobay et al, 2020). All known beetle bioluminescence system depend on a common substrate (S)-2-(6-hydroxy-2-benzothiazolyl)-2-thiazoline-4carboxylic acid, commonly known as D-luciferin (Figure 1), which consists of two structural units, benzothiazole and thiazoline rings (Shimomura and Yampolsky, 2019).…”
Section: D-luciferin-dependent Systemsmentioning
confidence: 99%
“…A number of coelenterazine-utilizing luciferases are well known, including those of soft corals (Renilla), copepods (Gaussia, Metridia) and decapods (Oplophorus) (Kotlobay et al, 2020), while vargulin-dependent luciferases have been derived only from an ostracod lineage Cypridinidae (Hensley et al, 2021). Coelenterazine also serves as the light emitter in the Ca 2+binding photoproteins, such as aequorin and obelin (Head et al, 2000).…”
Section: Imidazopyrazinone-based Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously reported that the luminescence intensity of GLuc is 200-fold higher than those of FLuc and RLuc, and its thermostability is remarkably high. 10,11 More recently, small luciferases emitting bright light, such as TurboLuc, 12 Nano-Luc, 13 and artificial luciferase (ALuc) 14,15 were developed. TurboLuc 12 is a modified luciferase derived from the copepod Metridia pacifica (MpLuc1), which has a sequence similar to that of GLuc.…”
Section: ■ Introductionmentioning
confidence: 99%
“…14,15 The small luciferases, such as GLuc and NanoLuc, have been recently utilized because their small sizes can reduce the steric hindrance of the luciferase-fused proteins, leading to the increased maintenance of the native functions of the proteins. 11,17 Additionally, their small sizes have an advantage in the bioluminescence resonance energy transfer (BRET)based assays because the BRET signal is inversely proportional to the sixth power of the distance between luciferase and fluorescent chromophore. 18 The bright light emission can lead to extremely sensitive detections; moreover, their high thermostabilities are valuable for practical applications such as in public health inspections, food safety and diagnosis, and transportation.…”
Section: ■ Introductionmentioning
confidence: 99%